Web-Based Cash Contribution Monitoring Information System for Citizens in Graha Sudirman Indramayu Housing - Lubis Ghozali, Ahmad; Sari Bunga, Munengsih; Permana Putra, Willy; Juita Sari, Iis (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The payment system in economic transactions is experiencing rapid progress along with the development of sophisticated technology. Graha Sudirman is a housing located in Indramayu Regency, West Java. In the cash dues section of residents in the Graha Sudirman Indramayu housing, cash dues collection is still done conventionally by way of the coordinator collecting each resident's house and recording it through a cash book. However, the cash contributions that are collected are not transparent in the data on expenditures or the remaining balance, so that residents do not know the income and disbursements of cash contributions paid every month. This application is designed and implemented using the PHP programming language with MySQL, it can be concluded that with the Citizen Cash Contribution Monitoring application using a codeigniter framework it can help admins recap cash dues, expenses, remaining balances and can help coordinators be able to streamline their time in collecting cash contributions because In this application the coordinator only needs to verify cash contribution payments made by residents by transfer and make it easier for residents to make cash contribution payments, provide criticism and suggestions for housing, find out financial data such as cash contribution reports, and expense reports.